Securing Indigenous Dispossession Through Education: An Analysis of Canadian Curricula and Textbooks - Schaefli, Laura; Godlewska, Anne; Lamb, Christopher (Springer International Publishing, 2019)
Abstract We investigate the representation of colonialism and Indigenous peoples in K-12 education in Canada. Focusing on three provinces—Newfoundland and Labrador, Ontario, and British Columbia—we analyze strategies of inclusion and exclusion at play in Ministry of Education-approved primary and secondary curricula and textbooks. Drawing on findings from our larger research project, we discuss the implications of these strategies on student consciousness. Our examination suggests that in all three educational jurisdictions, students are learning a logic of relation premised on the disappearance of Indigenous peoples as sovereign, self-determining nations. Silence around Indigenous philosophies and territories, apologia for colonial incursions on Indigenous territories, and reinforcement of racialized hierarchies of being all work to minimize colonial violence and preclude imagination of distinct, vital, and self-determining Indigenous nations. Particularly troubling are the ways in which curricula and texts invite students to participate in the perpetuation of colonial modes of thought and action.